Multifunctional polyimide nanofiber aerogel as well as preparation method and application thereof

The preparation of polyimide nanofiber aerogel by combining electrospinning and liquid nitrogen expansion solves the problems of poor mechanical properties and complex preparation process in the prior art, and achieves efficient and simple multifunctional and excellent Performance aerogel.

CN119219963AActive Publication Date: 2024-12-31SHANDONG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411493936.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-31
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing nanofiber aerogel preparation methods have problems such as poor mechanical properties, complex preparation process and high cost, and it is difficult to quickly and easily obtain polyimide aerogels with good mechanical properties and multifunctions.

Method used

Polyamic acid nanofiber membranes were prepared by electrospinning, and then expanded in liquid nitrogen and subjected to thermal imidation to obtain a polyimide nanofiber aerogel with a multi-stage porous structure.

Benefits of technology

Aerogels with high specific tensile strength, good compression cycle resistance and low thermal conductivity are prepared in a few minutes, with low density and wide temperature tolerance, suitable for oil and water separation, sound absorption and heat insulation, etc. field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219963A_ABST
    Figure CN119219963A_ABST
Patent Text Reader

Abstract

The invention discloses multifunctional polyimide nanofiber aerogel as well as a preparation method and application thereof, and belongs to the technical field of aerogel materials. The preparation method comprises the following steps: preparing a polyamide acid solution; the polyamide acid solution is subjected to electrostatic spinning, and a polyamide acid nanofiber membrane is prepared; immersing the polyamide acid nanofiber membrane into liquid nitrogen for 1-10 minutes, and expanding to obtain a polyamide acid nanofiber aerogel precursor; and carrying out thermal imidization treatment on the polyamide acid nanofiber aerogel precursor to obtain the polyamide acid nanofiber aerogel. The preparation method provided by the invention does not need a long-time drying process, and is low in energy consumption, simple, convenient and efficient in preparation process; the prepared aerogel has a plurality of properties such as good mechanical property, heat-insulating property, sound-absorbing property and flame-retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel materials, and in particular to a multifunctional polyimide nanofiber aerogel and a preparation method and application thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As a new type of aerogel, electrospun nanofiber aerogel has shown broad application prospects in the fields of thermal insulation, sound absorption, flexible electronic devices, catalysis and energy storage due to its high specific surface area, high porosity, light weight and flexibility. At present, the preparation methods of nanofiber aerogel mainly include the reorganization of short-cut nanofibers, chemical foaming agent foaming, the use of liquid bath collectors and direct electrospinning. The method of constructing nanofiber aerogel by reorganization and freeze drying of short-cut nanofibers usually has poor mechanical properties due to the discontinuity of nanofibers. Composite aerogels that enhance interaction and multifunctionality by adding other components usually sacrifice density and porosity in exchange for mechanical properties. Although several other methods can prepare continuous nanofiber porous materials, these materials usually present a loosely stacked structure, and the interaction between their nanofibers is weak, so the mechanical strength is not significantly improved. In addition, the above-mentioned preparation methods usually involve long-term drying, complex preparation processes and high costs, which limit the application of nanofiber aerogels.

[0004] Therefore, how to provide a simple and rapid method for preparing polyimide aerogels with good mechanical properties and multifunctionality is an urgent problem to be solved. Summary of the invention

[0005] In view of this, the present invention provides a multifunctional polyimide nanofiber aerogel and a preparation method and application thereof. The preparation method of the present invention is simple and fast. The prepared polyimide nanofiber aerogel has a fluffy multi-level porous structure, can be stretched and compressed and has good flexibility, and also has the properties of low density, low thermal conductivity and wide temperature tolerance.

[0006] In a first aspect, the present invention provides a method for preparing a multifunctional polyimide nanofiber aerogel, comprising the following steps:

[0007] preparing a polyamic acid solution;

[0008] Electrospinning the polyamic acid solution to prepare a polyamic acid nanofiber membrane;

[0009] Immersing the polyamic acid nanofiber membrane in liquid nitrogen for 1 to 10 minutes to expand it and obtain a polyamic acid nanofiber aerogel precursor;

[0010] The polyamic acid nanofiber aerogel precursor is subjected to thermal imidization treatment to obtain the aerogel.

[0011] Preferably, the step of preparing the polyamic acid solution is specifically: reacting a diamine monomer with a dianhydride monomer in a polar solvent to obtain a polyamic acid solution.

[0012] Furthermore, the diamine monomer is selected from one or more of 4,4'-diaminodiphenyl ether (ODA) or p-phenylenediamine (PDA); the dianhydride monomer is selected from one or more of pyromellitic anhydride (PMDA), biphenyltetracarboxylic anhydride (BPDA), benzophenonetetracarboxylic anhydride (BPDA) or 4,4'-oxydiphthalic anhydride (ODPA); the polar solvent is selected from one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) or N-methylpyrrolidone (NMP).

[0013] Furthermore, the concentration of the polyamic acid solution is 10 to 20 wt %; the reaction temperature is -5 to 5° C., and the reaction time is 5 to 24 hours.

[0014] Preferably, the electrospinning parameters are: spinning voltage of 18-28 kV, liquid feeding speed of 0.5-1.2 mL / h, drum speed of 500-1000 rpm, and the distance between the needle and the drum of 10-20 cm.

[0015] Preferably, the thickness of the polyamic acid nanofiber membrane is 2 to 6 mm.

[0016] Preferably, after the electrospinning step, the method further comprises drying the prepared polyamic acid nanofiber membrane at 50 to 80° C. for 1 to 3 hours.

[0017] Preferably, the polyamic acid nanofiber membrane is immersed in liquid nitrogen for 2 to 5 minutes to expand to obtain a polyamic acid nanofiber aerogel precursor.

[0018] Preferably, the reaction temperature of the thermal imidization is 230-390° C., and the reaction time is 4-8 hours.

[0019] In a second aspect, the present invention provides a multifunctional polyimide nanofiber aerogel prepared by the above preparation method.

[0020] In a third aspect, the present invention provides the use of the multifunctional polyimide nanofiber aerogel as an oil-water separation material, a sound absorbing material or a heat insulating and flame retardant material.

[0021] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0022] (1) The present invention utilizes liquid nitrogen vaporization to generate a significant pressure difference between nanofibers, which can achieve expansion of 2D nanofiber membranes into 3D ultra-fluffy multi-level porous aerogels within a few minutes, without the need for a long drying process, with low energy consumption and a simple and efficient preparation process;

[0023] (2) The polyimide nanofiber aerogel prepared by the preparation method of the present invention exhibits excellent mechanical properties, including high specific tensile strength, good compression cycle tolerance (after 1,000 cycles, the compression strength still remains more than 60%, and the highest can reach more than 90%) and excellent flexibility that remains unchanged at ultra-low temperatures. Thanks to the low density and complex multi-level porous structure of the aerogel of the present invention, the aerogel exhibits excellent thermal insulation performance, with the lowest out-of-plane thermal conductivity less than 30 mW·m -1 ·K -1 .

[0024] (3) The aerogel of the present invention has excellent properties such as heat insulation, sound absorption, oil absorption and flame retardancy, so that it can be used as an oil-water separation material, sound absorption material or heat insulation and flame retardant material, and is expected to be used in aerospace, flexible electronic devices, catalysis and energy processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 The scanning electron microscope images are of the polyimide nanofiber aerogels prepared in Examples 1 to 3 of the present invention; wherein (a) and (d) are cross-sectional and surface SEM morphology images of Example 1, (b) and (e) are cross-sectional and surface SEM morphology images of Example 2, and (c) and (f) are cross-sectional and surface SEM morphology images of Example 3;

[0027] Figure 2 The specific tensile strength (a) and compressive stress-strain curve (b) of the polyimide nanofiber aerogel prepared in Examples 1 to 3 of the present invention;

[0028] Figure 3 The flexibility display diagrams of the polyimide nanofiber aerogels prepared in Examples 1 to 3 of the present invention at room temperature (a) and in liquid nitrogen (b);

[0029] Figure 4The overall and anisotropic thermal conductivities of the polyimide nanofiber aerogels prepared in Examples 1 to 3 of the present invention;

[0030] Figure 5 Thermogravimetric curves (a) and combustion test images (b) of the polyimide nanofiber aerogels prepared in Examples 1 to 3 of the present invention.

[0031] Figure 6 This is a diagram showing the oil-water separation capability of the polyimide nanofiber aerogel prepared in Examples 2 and 3 of the present invention;

[0032] Figure 7 It is the sound absorption coefficient of the polyimide nanofiber aerogel prepared in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0033] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0034] The present invention provides a method for preparing a multifunctional polyimide nanofiber aerogel, comprising the following steps:

[0035] preparing a polyamic acid solution;

[0036] Electrospinning the polyamic acid solution to prepare a polyamic acid nanofiber membrane;

[0037] Immersing the polyamic acid nanofiber membrane in liquid nitrogen for 1 to 10 minutes to expand it and obtain a polyamic acid nanofiber aerogel precursor;

[0038] The polyamic acid nanofiber aerogel precursor is subjected to thermal imidization treatment to obtain the aerogel.

[0039] The present invention prepares a polyamic acid nanofiber membrane by electrospinning, and then immerses the nanofiber membrane in liquid nitrogen. The liquid nitrogen vaporizes rapidly at room temperature, thereby generating a significant pressure difference between the nanofibers, and then the nanofiber membrane is stretched within 1 to 10 minutes, so that the 2D nanofiber membrane expands into a 3D ultra-fluffy multi-level porous aerogel. The polyamic acid nanofiber membrane can maintain flexibility in liquid nitrogen, which mainly depends on the flexibility of the molecular structure and the size effect of the nanofiber. Specifically: (1) Flexibility of molecular structure: The amide bonds and carboxyl groups contained in the polyamic acid molecular chain make its molecular structure have a certain flexibility. Even at extremely low temperatures (such as liquid nitrogen environment), the movement of the molecular chain is restricted, but it will not be completely rigid, which allows the polyamic acid to maintain a certain toughness and deformation ability at extremely low temperatures; (2) Size effect of nanofibers: Due to the extremely small diameter of the fiber (usually tens to hundreds of nanometers), the stress concentration effect of nanoscale materials is significantly reduced, and cracks are not easy to occur. This microstructure can effectively disperse stress and prevent the material from brittle fracture at low temperatures. Since the present invention does not need to redissolve or disperse the nanofiber membrane, the nanofibers have strong interactions, so an aerogel with good mechanical properties can be obtained without the need for time-consuming and energy-consuming steps such as vacuum freeze drying.

[0040] In the present invention, the step of preparing the polyamic acid solution is specifically: reacting a diamine monomer with a dianhydride monomer in a polar solvent to obtain a polyamic acid solution.

[0041] In the present invention, the diamine monomer is selected from one or more of 4,4'-diaminodiphenyl ether (ODA) or p-phenylenediamine (PDA); the dianhydride monomer is selected from one or more of pyromellitic anhydride (PMDA), biphenyltetracarboxylic anhydride (BPDA), benzophenonetetracarboxylic anhydride (BPDA) or 4,4'-oxydiphthalic anhydride (ODPA); the polar solvent is selected from one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc) or N-methylpyrrolidone (NMP). The present invention does not impose any special restrictions on the molar ratio of the diamine monomer and the dianhydride monomer, and the molar ratio commonly used in the art for preparing polyamic acid can be used.

[0042] In the present invention, the concentration of the polyamic acid solution is 10-20wt%, more preferably 14-18wt%. If the solid content is too high, the apparent viscosity of the polyamic acid spinning solution is too high, the fluidity is poor, and the polyamic acid fiber cannot be normally ejected through the spinneret. If the solid content is too low, the apparent viscosity of the polyamic acid spinning solution is too low, the ejection pressure is insufficient, and the polyamic acid fiber cannot be normally ejected through the spinneret.

[0043] In the present invention, the reaction temperature of the diamine monomer and the dianhydride monomer is -5 to 5°C, preferably in an ice bath; the reaction time is 5 to 24 hours, preferably 12 to 24 hours.

[0044] In the present invention, the electrospinning parameters are: spinning voltage is 18-28 kV, liquid feeding speed is 0.5-1.2 mL / h, drum speed is 500-1000 rpm, and the distance between the needle and the drum is 10-20 cm.

[0045] In the present invention, the thickness of the polyamic acid nanofiber membrane is 2 to 6 mm, and the thickness of the finally prepared polyimide nanofiber aerogel is 10 to 20 mm.

[0046] After the electrospinning step, the present invention further includes a step of drying the prepared polyamic acid nanofiber membrane at 50-80°C for 1-3 hours, which is to remove the residual solvent after electrospinning. Natural drying at room temperature may also be selected, and the corresponding drying time also needs to be extended. Those skilled in the art may select according to actual needs. The dried polyamic acid nanofiber membrane is then immersed in liquid nitrogen.

[0047] In the present invention, the polyamic acid nanofiber membrane is preferably immersed in liquid nitrogen for 2 to 5 minutes to expand to obtain a polyamic acid nanofiber aerogel precursor.

[0048] In the present invention, the reaction temperature of the thermal imidization is 230-390°C, and the reaction time is 4-8h. More preferably, the steps of the thermal imidization are: heating to 230-250°C, keeping warm for 0.5-2h; then heating to 290-310°C, keeping warm for 0.5-2h; then heating to 370-390°C, keeping warm for 0.5-2h. The thermal imidization treatment dehydrates and cyclizes the polyamic acid into polyimide, and at the same time fixes the porous morphology of the aerogel. The present invention does not impose any special restrictions on the steps of the thermal imidization treatment, and the steps of the thermal imidization treatment commonly used in the art can be used, which is usually carried out in a thermal imidization furnace, and the heating rate is preferably 1-5°C / min, and the reaction is carried out under inert gas conditions.

[0049] The present invention also provides a multifunctional polyimide nanofiber aerogel prepared by the above preparation method, which exhibits excellent mechanical properties, including high specific tensile strength, good compression cycle tolerance (after 1,000 cycles, the compression strength still remains more than 60%, and can reach more than 90%), and excellent flexibility that remains unchanged at ultra-low temperatures. Thanks to the low density and complex multi-level porous structure of the aerogel of the present invention, the aerogel also exhibits excellent thermal insulation performance, with a minimum out-of-plane thermal conductivity of less than 30 mW·m -1 ·K -1 .

[0050] The present invention also provides the use of the multifunctional polyimide nanofiber aerogel as an oil-water separation material or a heat-insulating flame-retardant material. The aerogel of the present invention has excellent heat-insulating, sound-absorbing, oil-absorbing and flame-retardant properties, so that it can be used as an oil-water separation material, a sound-absorbing material or a heat-insulating flame-retardant material, and is expected to be used in the fields of aerospace, flexible electronic devices, catalysis and energy processing.

[0051] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0052] Example 1

[0053] This embodiment provides a method for preparing a multifunctional polyimide nanofiber aerogel.

[0054] (1) Add 1.001 g of 4,4'-diaminodiphenyl ether (ODA) and 0.545 g of p-phenylenediamine (PDA) into a beaker, then add 23.56 g of DMF and stir in an ice-water bath until dissolved. Then slowly add 2.942 g of biphenyltetracarboxylic dianhydride (BPDA) and continue stirring for 24 h. Finally, an electrospinning solution with a polyamic acid (PAA) concentration of 16 wt% and a molar ratio of diamine to dianhydride of 1:1 was obtained.

[0055] (2) The electrospinning solution was loaded into a 10 mL syringe and electrospinning was performed at a voltage of 24 kV. The diameter of the electrospinning needle was 0.5 mm, the liquid feeding speed was 1 mL / h, the drum speed was 1000 rpm, the distance between the needle and the drum was 13 cm, the spinning time was 5 h, and a polyamic acid nanofiber membrane with a thickness of about 3 mm was obtained;

[0056] (3) drying the polyamic acid nanofiber membrane obtained in the above process at 60° C. for 2 h, and then immersing it in liquid nitrogen for 3 min to obtain a polyamic acid nanofiber aerogel precursor;

[0057] (4) The polyamic acid nanofiber aerogel precursor sample was placed in a tubular furnace, and the temperature was raised from room temperature to 240°C at a rate of 1.5°C / min in nitrogen for 1 hour, then raised to 300°C at the same rate for 1 hour, and then raised to 380°C at the same rate for 1 hour, and then cooled in the furnace to obtain a multifunctional polyimide nanofiber aerogel with a thickness of about 10 mm and a density of 65 mg / cm 3 .

[0058] Example 2

[0059] This embodiment provides a method for preparing a multifunctional polyimide nanofiber aerogel.

[0060] (1) Add 1.001 g of ODA and 0.545 g of PDA into a beaker, then add 23.56 g of DMF, and stir in an ice-water bath until all the diamine is dissolved. Then slowly add 2.962 g of BPDA and continue stirring for 24 h. Finally, an electrospinning solution with a PAA concentration of 16 wt% and a molar ratio of diamine to dianhydride of 1:1.007 is obtained;

[0061] (2) The electrospinning solution was loaded into a 10 mL syringe and electrospinning was performed at a voltage of 25 kV. The diameter of the electrospinning needle was 0.5 mm, the liquid feeding speed was 1 mL / h, the drum speed was 1000 rpm, the distance between the needle and the drum was 13 cm, the spinning time was 5 h, and a polyamic acid nanofiber membrane with a thickness of about 3 mm was obtained;

[0062] (3) drying the polyamic acid nanofiber membrane obtained in the above process at 60° C. for 2 h, and then immersing it in liquid nitrogen for 3 min to obtain a polyamic acid nanofiber aerogel precursor;

[0063] (4) The polyamic acid nanofiber aerogel precursor sample was placed in a tubular furnace, and the temperature was raised from room temperature to 240°C at a rate of 1.5°C / min in nitrogen for 1 hour, and then raised to 300°C at the same rate for 1 hour, and then raised to 380°C at the same rate for 1 hour, and then cooled in the furnace to obtain a multifunctional polyimide nanofiber aerogel with a thickness of about 15 mm and a density of 32 mg / cm 3 .

[0064] Example 3

[0065] This embodiment provides a method for preparing a multifunctional polyimide nanofiber aerogel.

[0066] (1) Add 1.001 g of ODA and 0.545 g of PDA into a beaker, then add 23.56 g of DMF, and stir in an ice-water bath until all the diamine is dissolved. Then slowly add 2.982 g of BPDA and continue stirring for 24 h. Finally, an electrospinning solution with a PAA concentration of 16 wt% and a molar ratio of diamine to dianhydride of 1:1.013 was obtained.

[0067] (2) The electrospinning solution was loaded into a 10 mL syringe and electrospinning was performed at a voltage of 26 kV. The diameter of the electrospinning needle was 0.5 mm, the liquid feeding speed was 1 mL / h, the drum speed was 1000 rpm, the distance between the needle and the drum was 13 cm, the spinning time was 5 h, and a polyamic acid nanofiber membrane with a thickness of about 3 mm was obtained;

[0068] (3) drying the polyamic acid nanofiber membrane obtained in the above process at 60° C. for 2 h, and then immersing it in liquid nitrogen for 3 min to obtain a polyamic acid nanofiber aerogel precursor;

[0069] (4) The polyamic acid nanofiber aerogel precursor sample was placed in a tubular furnace, and the temperature was raised from room temperature to 240°C at a rate of 1.5°C / min in nitrogen for 1 hour, then raised to 300°C at the same rate for 1 hour, and then raised to 380°C at the same rate for 1 hour, and then cooled in the furnace to obtain a multifunctional polyimide nanofiber aerogel with a thickness of about 20 mm and a density of 8.8 mg / cm 3 .

[0070] Test example

[0071] 1. Morphology analysis:

[0072] Figure 1 3 are scanning electron microscope images of the polyimide nanofiber aerogels prepared in Examples 1 to 3 of the present invention; wherein (a) and (d) are cross-sectional and surface SEM morphology images of Example 1, (b) and (e) are cross-sectional and surface SEM morphology images of Example 2, and (c) and (f) are cross-sectional and surface SEM morphology images of Example 3; it can be seen from the figure that the aerogel has a multi-level porous structure.

[0073] 2. Mechanical properties determination:

[0074] Figure 2 The specific tensile strength (a) and compressive stress-strain curve (b) of the polyimide nanofiber aerogel prepared in Examples 1 to 3 of the present invention are shown in the figure. As can be seen from the figure, the prepared aerogel has excellent mechanical properties and is stretchable and compressible. The aerogel in Example 3 has a tensile strength of up to 298.9 MPa·cm 3 ·g -1 Specific tensile strength.

[0075] Table 1 shows the compression cycle tolerance test of the polyimide nanofiber aerogels prepared in Examples 1 to 3 under a compression strain of 70%. It can be seen from Table 1 that the compression strength retention rate of the aerogels in Examples 1 to 3 can reach more than 60% after 1000 cycles, and can reach more than 90% at the highest.

[0076] Table 1 Compression cycle resistance

[0077] serial number Initial compression strength Compression strength after 1000 cycles Compression strength retention rate (%) Example 1 140kPa 96.6kPa 69% Example 2 56.5kPa 46.3kPa 82% Example 3 12.9kPa 12.2kPa 94%

[0078] Note: The compression strength retention rate in Table 1 refers to the compression strength retention rate after 1000 cycles.

[0079] Figure 3 The flexibility of the polyimide nanofiber aerogel prepared in Examples 1 to 3 of the present invention at room temperature (a) and in liquid nitrogen (b) is demonstrated; it can be seen from the figure that the aerogel exhibits good flexibility and deformation recovery ability both at room temperature and in liquid nitrogen.

[0080] 3. Thermal conductivity determination:

[0081] Figure 4 The overall and anisotropic thermal conductivities of the polyimide nanofiber aerogels prepared in Examples 1-3 of the present invention; it can be seen from the figure that all aerogels exhibit low thermal conductivity, and the overall thermal conductivity is less than 50 mW·m -1 ·K -1 , the lowest can be as low as 30mW·m -1 ·K -1 the following.

[0082] 4. Heat resistance and flame retardancy determination:

[0083] Figure 5 Thermogravimetric curves (a) and combustion test pictures (b) of polyimide nanofiber aerogels prepared in Examples 1 to 3 of the present invention; it can be seen from the figure that the aerogel exhibits good temperature tolerance, and the temperature of 5% mass loss is nearly 600°C; and there is no open flame and no molten droplets when it burns, showing good flame retardancy.

[0084] 5. Determination of oil absorption performance:

[0085] Figure 6 The oil-water separation ability of the polyimide nanofiber aerogel prepared in Examples 2 and 3 of the present invention is demonstrated. It can be seen that the aerogel exhibits good oil-water separation performance; the polyimide nanofiber aerogel in Example 1 has a similar oil-water separation ability, which indicates that the polyimide nanofiber aerogel prepared in the present invention has application prospects in the field of oil-water separation.

[0086] 6. Sound absorption performance measurement:

[0087] Figure 7 The sound absorption coefficients of the polyimide nanofiber aerogels prepared in Examples 1 to 3 of the present invention show that the aerogels have different sound absorption coefficients and maximum absorption frequencies due to different pore structures. The polyimide nanofiber aerogel in Example 3 has the highest sound absorption coefficient of 0.94 at 2720-2976 Hz, showing good sound absorption performance.

[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a multifunctional polyimide nanofiber aerogel, characterized in that: The steps include: preparing a polyamic acid solution; Electrospinning the polyamic acid solution to prepare a polyamic acid nanofiber membrane; Immersing the polyamic acid nanofiber membrane in liquid nitrogen for 1 to 10 minutes to expand it and obtain a polyamic acid nanofiber aerogel precursor; The polyamic acid nanofiber aerogel precursor is subjected to thermal imidization treatment to obtain the aerogel.

2. The preparation method according to claim 1, characterized in that The step of preparing the polyamic acid solution is specifically: reacting a diamine monomer with a dianhydride monomer in a polar solvent to obtain a polyamic acid solution.

3. The preparation method according to claim 2, characterized in that: The diamine monomer is selected from one or more of 4,4'-diaminodiphenyl ether or p-phenylenediamine; the dianhydride monomer is selected from one or more of pyromellitic dianhydride, biphenyltetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride or 4,4'-oxydiphthalic anhydride; and the polar solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone.

4. The preparation method according to claim 2, characterized in that: The concentration of the polyamic acid solution is 10 to 20 wt %; the reaction temperature is -5 to 5° C., and the reaction time is 5 to 24 hours.

5. The preparation method according to claim 1, characterized in that: The electrospinning parameters are: spinning voltage of 18-28 kV, liquid feeding speed of 0.5-1.2 mL / h, drum speed of 500-1000 rpm, distance between needle and drum of 10-20 cm; the thickness of the polyamic acid nanofiber membrane is 2-6 mm.

6. The preparation method according to claim 1, characterized in that: After the electrospinning step, the method further includes drying the prepared polyamic acid nanofiber membrane at 50 to 80° C. for 1 to 3 hours.

7. The preparation method according to claim 1, characterized in that: The polyamic acid nanofiber membrane is immersed in liquid nitrogen for 2 to 5 minutes to expand to obtain a polyamic acid nanofiber aerogel precursor.

8. The preparation method according to claim 1, characterized in that: The reaction temperature of the thermal imidization is 230-390° C., and the reaction time is 4-8 hours.

9. The multifunctional polyimide nanofiber aerogel prepared by the preparation method according to claim 8.

10. Use of the multifunctional polyimide nanofiber aerogel according to claim 9 as an oil-water separation material, a sound absorbing material or a heat insulating and flame retardant material.

Citation Information

Patent Citations

  • Silicon dioxide nanofiber / polyimide composite aerogel as well as preparation method and application thereof

    CN113461364A

  • Flame-retardant and heat-insulating polyimide nanofiber aerogel and preparation method thereof

    CN113683812A

  • Nanofiber-reinforced semi-interpenetrating network structure polyimide composite aerogel and preparation method thereof

    CN114350010A

  • Preparation method of flame-retardant and heat-insulating fiber-reinforced polyimide aerogel

    CN117186479A

  • Flexible polyimide aerogel with high tensile strength as well as preparation method and application of flexible polyimide aerogel

    CN118221996A